Electrophysiological differences of deep sedation with dexmedetomidine versus propofol. (19th May 2022) - Servatius, H; Kueffer, T; Baldinger, SH; Asatryan, B; Seiler, J; Tanner, H; Novak, J; Noti, F; Haeberlin, A; Madaffari, A; Muehl, A; Branca, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Dexmedetomidine and propofol are commonly used drugs for deep sedation during cardiovascular interventions. Patients undergoing these interventions often have impaired sinus node function or atrioventricular (AV) conduction disease. Anesthetics used for deep sedation may further compromise sinus node function and AV nodal conduction, and thereby interfere with the intervention. Purpose: To compare the electrophysiological effects of dexmedetomidine and propofol on the function of the sinus node and AV conduction. Methods: We randomized patients undergoing first atrial fibrilation ablation 1:1 to deep sedation by dexmedetomidine (DEX group) versus propofol (PRO group), according to a standardized protocol. At the end of the ablation procedure with the patients still deeply sedated and hemodynamically stable, we conducted a standard electrophysiological study and assessed sinus node function, properties of AV conduction and atrial refractoriness. Results: Of 160 patients (65±11 years old; 32% female) included into the study, 80 patients were randomized to the DEX and PRO group each. Procedure duration (128±59 minutes) and sedation depth, as assessed by the "Modified Observer's Assessment of Alertness/Sedation" score (median 3; interquartile range 2, 3), was not different among groups. DEX group patients received a mean of 231±111 mcg of dexmedetomidine and PRO group patients a mean of 657±356 mg of propofol. The table shows the results of the electrophysiological study. DEX group patients had lower sinus rate and longer unadjusted sinus node recovery time (SNRT) at pacing cycle lengths of 600, 500 and 400 ms. However, both corrected (SNRT-RR) and normalized (SNRT/RR) SNRT did not differ among groups. Compared to PRO group patients, AV nodal conduction was slower in DEX group patients as evidenced by longer PR and AH intervals, and a higher Wenckebach cycle length and AV node effective refractory period (ERP) was observed. Conduction properties in the His-Purkinje system were not different among groups, as QRS width and HV interval were similar. An arrhythmia, mainly atrial fibrillation, was induced in 33 patients (21%) during the electrophysiological study, without differences among groups. Conclusions: Sinus rate and AV conduction are slower during deep sedation with dexmedetomidine compared to propofol. These differences in electrophysiological effects need to be taken into account when using these anesthetics during cardiovascular interventions.